2017
DOI: 10.1177/1474515117746011
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in phase II cardiac rehabilitation attendance: The impact of potential mediators

Abstract: Our study demonstrated a variety of mechanisms contributing to cardiac rehabilitation non-attendance. Further, the study demonstrated that non-attendance was especially related to the cardiac rehabilitation elements involving lifestyle modifications. However, the mechanisms explaining social inequality in full cardiac rehabilitation are still not fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
(57 reference statements)
2
22
2
Order By: Relevance
“…[29][30][31] The population characteristics of patients in our study were similar to other studies on patients with cardiac disease: 60-yearold men, typically overweight, having comorbidities and living with a partner. 13,29,32,33 However, the patients in our intervention group seemed to have a higher educational level, which has also been reported in a previous study. 29 This is important to consider, because low education has shown to be strongly linked to low health literacy and health behaviour.…”
Section: Generalisabilitysupporting
confidence: 86%
“…[29][30][31] The population characteristics of patients in our study were similar to other studies on patients with cardiac disease: 60-yearold men, typically overweight, having comorbidities and living with a partner. 13,29,32,33 However, the patients in our intervention group seemed to have a higher educational level, which has also been reported in a previous study. 29 This is important to consider, because low education has shown to be strongly linked to low health literacy and health behaviour.…”
Section: Generalisabilitysupporting
confidence: 86%
“…In cardiac rehabilitation, a recent study found that comorbidities, self-efficacy, anxiety and depression, cohabitation, commute, disease severity or type of treatment do not significantly mediate the association of SES with attendance and participation. 9 However, health literacy and communication between physician and patient are discussed to generally explain healthcare inequalities, as they are strongly associated with SES. 10–12 Although there is no clear evidence regarding whether an increase in treatment rates reduces socioeconomic disparities in access to treatment, 13 14 Perelman et al found that socioeconomic inequalities in CHD treatment can be partly explained by different distances to hospitals with on-site cardiac facilities.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the purpose of the quantitative component was to investigate potential factors associated with CR non‐attendance and to assess if these were differentially distributed among educational groups (Pedersen, Egerod, Overgaard, Baastrup, & Andersen, ). The purpose of the qualitative component was to explore the patient experience of barriers to completion of CR among different SEP groups (Pedersen, Overgaard, Andersen, Baastrup, & Egerod, ).…”
Section: The Studymentioning
confidence: 99%